2022
DOI: 10.48550/arxiv.2206.10271
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the discrete Safronov-Dubovskii coagulation equation: well-posedness, mass-conservation and asymptotic behaviour

Abstract: The existence and uniqueness of global classical solutions to the Safronov-Dubovskii coagulation equation are established for the coagulation kernels satisfying the linear growth condition i.e. γ i,j ≤ A(i δ + j δ ) for some δ ∈ [0, 1] which extends the results obtained in [6]. In particular, the initial condition may have an infinite second moment as long as δ < 1. Moreover, the solution constructed herein is shown to be mass-conserving. In the end, the continuous dependence on the initial data and the large-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…This, however, is not always the case. In [6,7,19,22], it is observed that for the discrete smoluchowski coagulation equations (1.1)-(1.2), the mass conservation property fails for coagulation kernels of the form γ i,j ≥ (ij) α 0 2 , where α 0 ∈ (1,2]. It is worth noting that gelation also occurs in the DSDC equations, and we get the same result as in the discrete Smoluchowski coagulation equation.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…This, however, is not always the case. In [6,7,19,22], it is observed that for the discrete smoluchowski coagulation equations (1.1)-(1.2), the mass conservation property fails for coagulation kernels of the form γ i,j ≥ (ij) α 0 2 , where α 0 ∈ (1,2]. It is worth noting that gelation also occurs in the DSDC equations, and we get the same result as in the discrete Smoluchowski coagulation equation.…”
Section: Introductionsupporting
confidence: 66%
“…Unfortunately, the coagulation kernel Λ i,j = i + j is not included in either of the classes (2.2) or (2.3). Although the existence result for this kernel is available in the literature, see [1,8,15].…”
Section: Main Results and Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation